HUMANIZATION OF ORGANIZATIONAL EFFICIENCY IN ISLAMIC EDUCATION: A CLASSICAL AND NEOCLASSICAL SYNTHESIS APPROACH TO MADRASAH MANAGEMENT - Diana, Merita; Febriana, Wahyu; Subandi, Subandi; Syarifudin, Encep (Institut Bakti Nusantara, 2025)
This study aims to analyze the synthesis of structural efficiency and organizational humanization in Islamic primary school management by integrating classical, neoclassical, and modern organizational theories. The research is motivated by the dominance of administrative-oriented managerial practices, while humanistic and systemic dimensions remain insufficiently integrated into Islamic primary school management. A qualitative approach with a case study design was employed at MIS Roudtul Atfal Pagelaran. Data were collected through in-depth interviews, observations, and document analysis involving the principal, teachers, and administrative staff as research participants. Data analysis followed the interactive model of Miles and Huberman and was supported by NVivo software to enhance analytical rigor and transparency. The findings reveal that school management is still largely characterized by structural efficiency reflected in formal task distribution and orderly administrative procedures. However, organizational humanization emerges through informal communication, harmonious social relations, and facilitative school leadership. Furthermore, the implementation of a systems approach and the utilization of information technology remain at an early stage and do not yet fully reflect the characteristics of a T-Form organization. This study concludes that synthesizing structural efficiency and humanistic approaches is essential for developing effective, adaptive, and sustainable Islamic primary school management. The findings contribute empirically to the development of an integrative management model that balances organizational efficiency with human values and Islamic ethics.